Long-term follow-up confirms a survival advantage of the paclitaxel–cisplatin regimen over the cyclophosphamide–cisplatin combination in advanced ovarian cancer. (1st October 2003) - Piccart, M. J.; Bertelsen, K.; Stuart, G.; Cassidy, J.; Mangioni, C.; Simonsen, E.; James, K.; Kaye, S.; Vergote, I.; Blom, R.; Grimshaw, R.; Atkinson, R.; et al.
Abstract : Two independent and consecutive randomized clinical trials, conducted by the American Gynecological Oncology Group and by an European–Canadian Intergroup, have shown superiority, in clinical response rate, progression-free survival, and overall survival, of a cisplatin–paclitaxel regimen over cisplatin–cyclophosphamide given as first-line chemotherapy for women with advanced epithelial ovarian cancer. The results of these studies, published with a median follow-up of about 3 years, have been updated with a 6.5-year follow-up: In each case, an 11% absolute gain in survival favoring the paclitaxel arm is shown; this advantage remains both statistically and clinically significant and supports a role for paclitaxel in frontline chemotherapy for advanced ovarian cancer.